Bi‐modified SrTiO3‐based ceramics for high‐temperature energy storage applications. Issue 3 (22nd October 2019) - Kong, Xi; Yang, Letao; Cheng, Zhenxiang; Zhang, Shujun
Abstract: Dielectric capacitors with high energy storage performance are in great demand for emerging advanced energy storage applications. Relaxor ferroelectrics are one type dielectric materials possessing high energy storage density and energy efficiency simultaneously. In this study, 0.9(Sr0.7 Bi0.2 )TiO3 –0.1Bi(Mg0.5 Me0.5 )O3 (Me = Ti, Zr, and Hf) dielectric relaxors are designed and the corresponding energy storage properties are investigated. The excellent recoverable energy density of 3.1 J/cm 3 with a high energy efficiency of 93% is achieved at applied electric field of 360 kV/cm for 0.9(Sr0.7 Bi0.2 )TiO3 –0.1Bi(Mg0.5 Hf0.5 )O3 (0.9SBT–0.1BMH) ceramic. High breakdown strength of 460 kV/cm in 0.9SBT–0.1BMH ceramic is obtained by Weibull distribution with satisfied reliability. In addition, 0.9SBT–0.1BMH shows outstanding thermal stability of energy storage performance up to 200°C, with the variation being less than 5%, together with satisfying cycling stability and high charge‐discharge rate, making the 0.9SBT–0.1BMH ceramic a potential lead‐free candidate for high power energy storage applications at elevated temperature.